Spatial density and distribution of tumor-associated macrophages predict survival in non–small cell lung carcinoma - Zheng, Xiang; Justus Liebig University Giessen (My University, 2021)
The respective antitumoral and protumoral roles of M1 and M2 tumor-associated macrophages (TAM) typify the complexity of macrophage function in cancer. In lung cancer, density and topology of distinct TAM phenotypes at the tumor center (TC) versus the invasive margin (IM) are largely unknown. Here, we investigated TAM subtype density and distribution between TC and IM in human lung cancer and TAM associations with overall survival. Macrophages isolated from adjacent nontumor tissue (NM), the TC (TC-TAM), and the IM (IM-TAM) were analyzed with RNA-sequencing (RNA-seq). Lung tumor tissue microarrays from 104 patient samples were constructed. M1 and M2 TAMs were identified using multiplex immunofluorescence staining and a tumor cell-TAM proximity analysis was performed. RNA-seq identified marked differences among NM, TC-TAM, and IM-TAM. On the basis of a panel of five selected markers (CD68, IL12, CCR7, CD163, and ALOX15), M2 predominance over M1 and M2 proximity to tumor cells was observed, especially at IM. Tumor cell proximity to TAM was linked with tumor cell survival and hypoxia was associated with accumulation of M2 TAM. Notably, lower density of M1 TC-TAM and higher proximity of tumor cells to M2 IM-TAM or lower proximity to M1 IM-TAM were linked with poor survival. In addition, three novel molecules (UBXN4, MFSD12, and ACTR6) from RNA-seq served as potential prognostic markers for lung cancer, and M2 predominance and juxtaposition of M2 TAM near tumor cells were associated with poor survival. Together, our results reveal the marked heterogeneity of TAM populations in different tumor regions, with M2 TAM predominance, particularly at IM.
Keywords: Lung cancer; Tumor-associated macrophages; Prognostic marker; Multiplexing; Spatial distribution; ddc:570; ddc:610